COMMUNICATION, WORK DISCIPLINE AND MANAGEMENT OF SCHOOL HEADS TO THE TEACHING PERFORMANCE OF HIGH SCHOOL TEACHERS IN AMBON CITY - ZACHARIAS TEHUBIJULUW (Fakultas Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to analyze the influence of communication, work discipline and school principal management on the teaching performance of Ambon Public senior high school Â teachers. This research is applied research with associative explanatory level. The population in this study were all teachers in the Ambon Public senior high school as many as 44 people. Data were analyzed by multiple linear regression. The results showed that: (1) communication, discipline and management of school principals partially influenced the teaching performance of teachers, (2) discipline was the dominant variable that affected teacher teaching performance, (3) communication, discipline and management of principals simultaneously influenced on teacher teaching performance.